The Population Attributable Fraction (PAF) of cases due to gatherings and groups with relevance to COVID-19 mitigation strategies - Brooks-Pollock, Ellen; Read, Jonathan M.; House, Thomas; Medley, Graham; Keeling, Matt J.; Danon, Leon
Background Many countries have banned groups and gatherings as part of their response to the pandemic caused by the coronavirus, SARS-CoV-2. Although there are outbreak reports involving mass gatherings, the contribution to overall transmission is unknown. Methods We used data from a survey of social contact behaviour that specifically asked about contact with groups to estimate the Population Attributable Fraction (PAF) due to groups as the relative change in the Basic Reproduction Number when groups are prevented. Findings We estimate that PAF due to groups of 50+ people is 2.2% (95%CI 1.1%, 3.6%); the PAF due to groups of 20+ people is 6.4% (5.0%, 8.0%); the PAF due to groups of 10+ is 11.3% (9.9%, 13.0%) Interpretation Large groups of individuals have a small epidemiological impact; small and medium sized groups between 10 and 50 people have a larger impact on an epidemic.
Keywords: Coronavirus; COVID-19; Population Attributable Fraction